Estudo comparativo entre picossulfato de sódio e macrogol no preparo intestinal para colonoscopia - Rosa, Taís Fini (2024)
Introduction: Colonoscopy is essential for colorectal cancer’s screening and diagnosis and other gastrointestinal pathologies, such as precancerous polyps. High-quality bowel preparation is critical for optimal visualization, precise lesion margin identification, and safe and complete endoscopic resections. This study evaluates two bowel preparation methods’ quality and the patient satisfaction. Objective: To compare the efficacy and tolerability of two bowel preparation solutions, Picoprep® and Peg-Lax®, using the Boston Bowel Preparation Scale (BBPS) to assess preparation quality, and a patient satisfaction questionnaire. Methods: A prospective study was conducted with 216 participants randomly assigned into two 108 individuals’ groups. Group 1 used Picoprep® (sodium picosulfate) while Group 2 used Peg-Lax® (Macrogol 3350). Both groups followed a clear liquid diet the day before colonoscopy and ingested four Ducolax tablets in the morning, followed by their respective bowel preparation solutions. The BBPS was employed to grade bowel preparation quality, and a questionnaire assessed patient satisfaction. Sample size calculations used a standard deviation of 30, a 95% confidence interval, and a 4% margin of error, resulting in a target of 219 participants. Results: A total of 396 patients were analyzed, with 200 (50.5%) in Peg-Lax® group and 196 (49.5%) in Picoprep® group. Picoprep® group showed a higher proportion on BBPS’s 3 scores, indicating colonic mucosa’s excellent visualization with no significant residual coloration, stool fragments or opaque liquid. Conversely, Peg-Lax® group had a higher frequency of 2 scores, characterized by some residual coloration and small stool fragments, but with mucosa’s good visibility. There was no significant difference in bowel preparation’s overall adequacy between two groups, with over 89% of cases rated as adequate in both groups. Regarding adverse effects, Picoprep® group exhibited a significantly higher occurrence of general symptoms, including anal irritation, while Peg-Lax® group reported a higher incidence of nausea. Conclusion: Both Picoprep® and Peg-Lax® were effective bowel preparation methods, albeit with different tolerability profiles. The choice between these preparations should be individualized, considering patients' clinical characteristics, preferences and specific contraindications. Future multicenter studies with larger sample sizes and subgroup analyses, including elderly patients and those with comorbidities, are necessary to delineate more wisely preferred indications for each preparation method.